2017
DOI: 10.3791/55641
|View full text |Cite
|
Sign up to set email alerts
|

<em>In Vitro</em> Growth of Mouse Preantral Follicles Under Simulated Microgravity

Abstract: 14 day-old mouse ovarian tissue and preantral follicles isolated from same-aged mice were incubated in a simulated microgravity culture system. We quantitatively assessed follicle survival, measured follicle and oocyte diameters, and examined ultrastructure of the oocytes produced from the system. We observed decreased follicle survival, downregulation of expressions of proliferating cell nuclear antigen and growth differentiation factor 9, as indicators for the development of granulosa cells and oocytes, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…To support the interpretations of the SEM results, the follicles isolated by the enzymatic method were cultured for 24 h. This short-culture has been shown to be an effective procedure in the evaluation of follicular viability as the follicular damage appears only after a few hours, when the follicle returns to its physiological conditions in which case follicular growth does not occur anymore (Vanhoutte et al, 2004). In the present study, peccary PF viability was confirmed using fluorescent probes that confirmed the presence of an intact basal membrane around isolated follicles, similar to that for domestic swine (Ahn et al, 2012), sheep (Lakshminarayana et al, 2014), and mice (Zhang et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…To support the interpretations of the SEM results, the follicles isolated by the enzymatic method were cultured for 24 h. This short-culture has been shown to be an effective procedure in the evaluation of follicular viability as the follicular damage appears only after a few hours, when the follicle returns to its physiological conditions in which case follicular growth does not occur anymore (Vanhoutte et al, 2004). In the present study, peccary PF viability was confirmed using fluorescent probes that confirmed the presence of an intact basal membrane around isolated follicles, similar to that for domestic swine (Ahn et al, 2012), sheep (Lakshminarayana et al, 2014), and mice (Zhang et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…Cultivation in simulated weightlessness of mouse preantral follicles in vitro revealed disruption of microvilli in the zona pellucida , the presence of vacuolized mitochondria and cytoplasmic vacuoles [ 110 ], and a decrease in follicle survival, probably due to aberrant development of granulosa cells [ 111 ]. In another experiment, Kunming mouse oocytes were harvested at the germinal vesicle stage (which is the metaphase of the first meiotic division) by superovulation stimulation.…”
Section: Gametsmentioning
confidence: 99%
“…The reasons for these failures could be related both to the difficulties of conducting an experiment in space flight conditions and to the characteristics of the early embryogenesis of mammals and the maturation of their germ cells. For example, under simulated microgravity conditions by a random positioning machine, a decrease in the survival of mouse follicles was observed with aberrant development of granulosa cells and oocytes, as shown by a reduction in the content of related markers [ 4 ].…”
Section: Introductionmentioning
confidence: 99%